THE INFLUENCE OF PARENTS’ EDUCATION AND LEARNING MOTIVATION ON MATHEMATICS LEARNING ACHIEVEMENT AT SD NEGERI KRAMAT III - WIJAYA, SUKMA (JPSD (Jurnal Pendidikan Sekolah Dasar), 2025)
This research aims to analyze how education carried out by parents and learning encouragement affects students’ mathematics learning achievement, individually and collectively. If there is indeed a very positive and significant influence, then how strong is the influence of education carried out by parents and learning motivation on students’ mathematics learning achievement? The research method used is after-the-fact. This research selected 45 respondents as the research sample. The researchers collected data using a questionnaire and analyzed it with descriptive statistical methods, including calculating the mean, median, mode, and standard deviation. This research used statistical tests to analyze the significance of the correlation coefficient with the t-test. The research was carried out from January to June 2024. The results show that: 1) parents’ education significantly influences students’ mathematics learning achievement. The obtained tcount proves a score of 2.199 and Sig. 0.033<0.05. The parents’ education variable contributes 16.66% to improving students’ mathematics learning achievement. 2). Learning motivation significantly influences students’ mathematics learning achievement. The obtained tcount proves a score of 3.063 and Sig. 0.004 < 0.05. The learning motivation variable contributes 25.51% in improving students’ Mathematics learning achievement. 3) Parents’ education and learning motivation significantly influence students’ mathematics learning achievement. The evidence was shown by obtaining a score of Fo = 15.298 and Sig. 0.000 < 0.05. Together, education carried out by parents and learning motivation affect the mathematics learning achievement obtained by students, contributing 42.1%.